Listen to me: why narrative medicine matters in healthcare - Magalhães, Susana Teixeira (Advances in Social Sciences Research Journal, 2019)
In contemporary societies, the relationship between patients and health professionals is undergoing substantial changes, together with the growing recognition of the former as active participants in deliberation and decision making on the management of their condition. Accordingly, adequate knowledge of disease/illness is necessary to set up a dialogue between patients/citizens and experts/professionals. In the health field, narratives constitute the axial point between distinct but complementary realities, emphasizing that the physiological meaning of disease falls short of individual and social translation. These renewed alignments of experiential and biomedical knowledge determine not only physicians’ involvement, but they also require reconsidering the training of health and humanities students and their role in the care of patients. Moreover, hospital managers, journalists, civil organizations, government and patients’ associations are elicited to participate in the outline of new borders and new landscapes in healthcare. The intra-subjective and inter-subjective dimensions of Medicine include not only the patient–doctor encounter, but also all the other members of the therapeutic relationship – relatives, other health professionals, community –, including teams and organizations. Listening to all these participants in healthcare is mandatory in order to face the ethical, scientific and technological challenges of a fast changing world. Narrative Medicine provides the tools and the skills to promote listening, interpretation, representation and affiliation, standing out as the interdisciplinary field of knowledge that can build the bridge to the future of a more humane healthcare.